Stem anatomy of dalbergia and diospyros species from Madagascar : with a special focus on wood identification - Ravaomanalina, Bako Harisoa; Crivellaro, Alan; Schweingruber, Fritz Hans (Springer, 2017)
This atlas offers anatomical descriptions of 19 Dalbergia and 31 Diospyros species, most of them endemic to Madagascar. Each species is illustrated with color micrographs of double-stained sections through the xylem, bark, and pith of stems, branches, and twigs. Further, a photograph of each plant and information on its height, DBH, habit, and geographical and elevational distribution in Madagascar are included. Dalbergia and Diospyros species provide highly-priced woods, which are intensively traded across the world and therefore highly endangered by illegal trade and harvesting. This book represents a response to the action plan for Diospyros and Dalbergia species regarding the establishment of a reference collection and reliable identification system for species listed by CITES, the Convention on International Trade in Endangered Species of Wild Fauna and Flora. Bringing together a wealth of material recently collected in different biogeographical regions of Madagascar and identified by the Missouri Botanical Garden, the book will appeal to plant scientists, taxonomists and practitioners involved in wood identification, and will help to safeguard the legacy of precious wood trading through proper identification.
Keywords: Dalbergia -- Madagascar.; Diospyros -- Madagascar.; Madagascar.; elektronické knihy; electronic books